Influence of feed additives for chickens on the quality of eggs laid and related risks - Magdalena Wasielewska (Kazimierz Wielki University, 2021)
A chicken egg is a valuable animal product that has served people for centuries. Research carried out over the last dozen or so years shows that society's knowledge about them is still relatively small. The research cited in the text shows that only 23% of respondents know that the color of a hen's egg shell depends on the breed of the hen, and not on the way it is fed. As a result, some consumers choose eggs in the store by choosing their color instead of the official markings on each individual egg. Chickens' nutrition has a direct impact on the quality of the eggs they lay. Chickens fed with fodder with antibiotics lay eggs in which we can find the same antibiotics that the animal ate with the food. It has many side effects, however, the greatest of which seems to be bacterial drug resistance, caused by the use of the same strong antibiotics in the nutritional industry and in human hospital medicine. Bacteria have developed various resistance mechanisms. For example, Enterococcus spp. Has developed resistance to vancomycin, Salmonella Typhimurum to tetracyclines, sulfonamides and fluoroquinolones. However, it is possible to use antibiotics in poultry treatment, but it is very important in this case to strictly observe the grace periods necessary to eliminate the antibiotic from the animal's body. Some of the world's governments, aware of the dangers of such a state of affairs, are trying to combat the phenomenon of feeding poultry with antibiotic growth stimulants by introducing new norms, orders and bans in their countries. Antibiotics such as avoparcin, zinc-bacitracin and spiromycin have been discontinued. Chicken egg producers are finding newer and newer ways to circumvent these recipes. Non-antibiotic feed additives such as probiotics, phytobiotics, and specific herbs are used. An effective way to combat this phenomenon may be to educate the public on this topic.